2018
DOI: 10.1016/j.arthro.2018.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Goldilocks and the Three Grafts: Managing Tendon Harvest and Graft Length Problems in Autograft Anterior Cruciate Ligament Reconstruction

Abstract: Autograft hamstring tendon harvest in anterior cruciate ligament (ACL) reconstruction can occasionally result in a graft length that is inadequate for creation of a robust ACL graft. Patients at risk for an abnormally short hamstring may also be high risk for ACL reinjury. Graft augmentation with allograft may be a suboptimal solution to this problem. Therefore, a reliable means for preoperative estimation of hamstring tendon length by magnetic resonance imaging measurement could avoid this pitfall. However, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Gilmer suggested that accurate preoperative assessment is more important than ever to prevent inadequate graft size before harvest. 23 If accurate information about intra-articular ACL length is known preoperatively, it could assist in making informed decisions about graft selection of adequate length for the specific patient. The mean ACL length was measured to be 40.6 mm on the oblique sagittal MRIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gilmer suggested that accurate preoperative assessment is more important than ever to prevent inadequate graft size before harvest. 23 If accurate information about intra-articular ACL length is known preoperatively, it could assist in making informed decisions about graft selection of adequate length for the specific patient. The mean ACL length was measured to be 40.6 mm on the oblique sagittal MRIs.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is a routine part of preoperative evaluation for ACL reconstruction and should be readily available to surgeons. 23 However, the reality is that the cost of MRI, the waiting periods, and the availability thereof in certain countries can be challenging. It would therefore be useful to have an alternative means by which the length of the ACL can be determined, should an MRI not be available.…”
mentioning
confidence: 99%